Geomatic techniques in forensic science: A review. Issue 2 (March 2020) - Berezowski, Victoria; Mallett, Xanthé; Moffat, Ian
Highlights: End goal of crime scene reconstruction is to obtain as much information as possible. Geomatic techniques allow scenes to be mapped and measured quickly and efficiently. Produce visually pleasing outputs that generate accurate and reliable measurements. To be used in conjunction with already established manual methods. Not to be used on every scene but to the investigator's discretion. Abstract: The purpose of this review paper is to highlight various geomatic techniques that crime scene reconstructionists or forensic practitioners can use to document different kinds of scenes, highlighting the advantages, disadvantages, and when best to use each technology. This paper explores geomatic techniques such as a total station, photogrammetry, laser scanners and structured light scanners and how they can be used to reconstruct crime scenes. The goal of this paper is not to discredit manual methods, as they are long standing and reliable, but instead to shed light on alternative methods that may produce equally or more accurate results with a more visually appealing final product. It is important for law enforcement and forensic professionals to understand the advantages and disadvantages of each technique, knowing when certain techniques should be used (and when they should not), and being able to revert to traditional methods if required.